Comparing Quality Parameters of Yarn Produced by Ring, Rotor, and Compact Spinning System - Islam, Zahidul (European Scientific Journal, ESJ, 2019)
The end use of a garment depends on the properties of a fabric. A fabric property depends on the properties of the constituent yarn. With the diversification of the market, spinners are forced to produce quality yarn. For this reason, conventional hand spinning has been converted to modern system gradually. Ring spinning, Rotor spinning, and compact spinning are widely used spinning system. Ring spinning is the universal spinning system covering the largest area of yarn production. The yarn produced by Ring, Compact, and rotor spinning systems belongs to different structures and properties. Yarn produced Ne 22’s, 100% cotton yarn from the above systems, and their properties were tested by UT5 and Titan Universal strength tester. However, this paper focuses on comparing the yarn properties (U%, CmV%, Imperfection, Hairiness, Strength, and elongation) of ring, compact, and rotor spun yarn. Also, it has been observed that yarn produced by compact spinning system revealed highest strength and elongation, least hairiness, and mass irregularity than the other two spinning systems. In addition, it has been observed that rotor spun yarn displayed less mass irregularity than ring spun yarn.